Water Erosion from Agricultural Land Under Atlantic Climate - Valcárcel, Montserrat; González, Antonio Paz; Dafonte, Jorge; Mirás-Avalos, José Manuel; Paz-Ferreiro, Jorge; Bertol, Ildegardis; Vázquez, Eva Vidal (IntechOpen, 2011)
None